The Use of Web Based Tests in an English Classroom: EFL Students Perceptions - Nur Adheliya Septiarananda; Istanti Hermagustiana; Satyawati Surya; Desy Rusmawaty (Journal of English Language Teaching, Literature and Culture, 2023)
One of the practical applications of technology integration in the educational field is a web based test Since students need to be involved in the classroom assessment decision knowing their perceptions toward the use of evaluation media is deemed important Thus this study was aimed to identify the students perceptions on the use of web based tests in an English class and to examine the problems experienced by students when using them in the classrooms One hundred fourteen high school students participated in this study This study utilized a survey which consisted of both open and close ended questions A google form based questionnaire was used to collect the data from the selected participants The data were analyzed by using descriptive statistical analysis The result of this study indicated that the students had positive perceptions of the use of web based tests However they experienced some problems during the implementation of the web based tests The problems include the mobile device breakdown lack of security unfamiliarity internet connection issue server failure browser incompatibility mobile device unavailability mobile device incompatibility and time limitation The study also found that the most frequent problem experienced by students was the server failure problem Some pedagogical implications of this study were discussed< em> < em>< p>